24-HOUR ARTERIAL STIFFNESS VALUES IN MEN WITH DIFFERENT PHENOTYPES OF CHRONIC OBSTRUCTIVE PULMONARY DISEASE CONCURRENT WITH HYPERTENSION - N. A. Karoli; G. R. Dolishnyaya; A. P. Rebrov (Klinicist)
Objective: to study the specific features of the daily arterial stiffness (AS) profile in men with different phenotypes of chronic obstructive pulmonary disease (COPD) concurrent with hypertension. Subjects and methods. The investigation enrolled 78 male patients with COPD and hypertension. The patients were divided according to COPD phenotypes into 2 groups: 1) COPD patients with emphysema; 2) those with bronchitis. The exclusion criteria were less than 40 years and more than 80 years of age; diabetes mellitus; coronary heart disease; vascular diseases; an exacerbation of chronic diseases; bronchial and pulmonary diseases of another etiology. The patients underwent 24-hour blood pressure and AS monitoring, external respiratory function testing: spirography with a short-acting β2-agonist test, a six-minute walk test at baseline and after a hemoglobin oxygen saturation test, and a CAT test. Results. The patients of both groups were observed to have a statistically significant increase in (dP/dt)max as compared to those of the control group (p < 0.05; p < 0.01) in both the daytime and nighttime. In these periods, the COPD patients with emphysema had a higher AIx than those with bronchitis (p < 0.001). There was a statistically significantly (p < 0.001) higher AIx in the nighttime than in the daytime in Groups 1 and 2 patients. Conclusion. The patients with different COPD phenotypes were noted to have impaired arterial elastic properties, circadian AS changes with predominantly nocturnal impaired vascular stiffness. Relationships were found between 24-hour AS values and clinicoanamnestic findings.